2020
DOI: 10.1371/journal.pmed.1003083
|View full text |Cite
|
Sign up to set email alerts
|

Health of Special Immigrant Visa holders from Iraq and Afghanistan after arrival into the United States using Domestic Medical Examination data, 2014–2016: A cross-sectional analysis

Abstract: Background Since 2008, the United States has issued between 2,000 and 19,000 Special Immigrant Visas (SIV) annually, with the majority issued to applicants from Iraq and Afghanistan. SIV holders (SIVH) are applicants who were employed by, or on behalf of, the US government or the US military. There is limited information about health conditions in SIV populations to help guide US clinicians caring for SIVH. Thus, we sought to describe health characteristics of recently arrived SIVH from Iraq and Afghanistan wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…A combined hepatitis B vaccine given at 6, 10, and 14 weeks of age as part of National Immunization Schedule were introduced in Nepal, Senegal, Malawi, Afghanistan, and Haiti in 2002 [31,32], 2002 [33], 2004 [34], 2006 [35], and 2012 [36,37] respectively. However, the birth dose was introduced only in 2014 in Afghanistan [35], while Senegal introduced the monovalent birth-dose vaccine in 2016 [34]. Yet, the Senegalese government lacks vaccination programme for high risk population such as HCWs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A combined hepatitis B vaccine given at 6, 10, and 14 weeks of age as part of National Immunization Schedule were introduced in Nepal, Senegal, Malawi, Afghanistan, and Haiti in 2002 [31,32], 2002 [33], 2004 [34], 2006 [35], and 2012 [36,37] respectively. However, the birth dose was introduced only in 2014 in Afghanistan [35], while Senegal introduced the monovalent birth-dose vaccine in 2016 [34]. Yet, the Senegalese government lacks vaccination programme for high risk population such as HCWs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated BLLs in Afghan children were also noted in a multistate study of Special Immigrant Visa (SIV) holders from Iraq and Afghanistan after arrival in the U.S. In 2014-2016, 47.8% of children from Afghanistan had BLLs of 5-9 μg/dL; 10.9% had BLLs of 10-19 μg/dL [13]. In an earlier study of resettled refugees who arrived in the U.S. between 2010 and 2014, children from Afghanistan had the highest prevalence of BLLs ≥ 10 μg/dL (16.7%) of children from any other country of origin [14].…”
Section: Afghan Refugee Children-a Population At Riskmentioning
confidence: 89%
“…Furthermore, malnutrition is higher among refugees living in poor socioeconomic conditions and is associated with TB prevalence and its reactivation [ 25 , 26 , 27 , 28 ]. In a recent study, Kumar et al (2020) found that the prevalence of latent TB infection among newly arriving refugees into the United States was significant high in Afghan population [ 29 ]. Hence, awareness for TB, strength of the surveillance strategies, compliance with measures to limit transmission and training of healthcare workers should be optimised.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Haq et al studied the prevalence of Giardia intestinalis and Hymenoleps in a cross-sectional analysis of Special Immigrant Visa holders from Afghanistan into the United States and found high prevalence (30.7%) of at least one intestinal parasite. The most commonly detected parasites were Blastocystis, Giardia, and Dientamoeba [ 29 ]. Given that parasitic diseases may cause severe and lethal diseases [ 47 ], prompt prevention and eradication therapies should be established, especially for this vulnerable population.…”
Section: Infectious Diseasesmentioning
confidence: 99%